Optimization of white light interferometry on rough surfaces based on error analysis - Saraç, Z; Gross, R; Richter, C; Wiesner, B; Häusler, G (Elsevier Gmbh, 2004)
White light interferometry can be used to measure the shape of rough surfaces. At rough surfaces, the measuring uncertainty in principle cannot be better than the surface roughness, which is commonly in the range of 1 micron. Hence, the requirements for the hard- and software components of the instrument are not as high as for interferometry in the nanometer regime. An analysis of the dominant error sources allows the design of an optimal sensor with a measuring uncertainty as small as physically possible, with components as good as necessary and as simple as possible.
Keywords: ehite light interferometry; measuring uncertainty